The Impact of Coverage Forms of Exterior Vertical Greening Walls on the Thermal Environmental Benefits of Buildings in Hot and Humid Regions - Li Li; Junfeng Cheng; Zhichao Liu; Qingliang Li; Lan Yu; Xiaoqing Zhou; Yue Pang (Buildings)
Architectural vertical green walls can mitigate the urban heat island effect, provide shade and cooling, reduce energy consumption, improve a microclimate, and increase indoor comfort. However, an excessive pursuit of high coverage may diminish the benefit ratio and adversely affect ventilation and lighting. Field measurements were conducted in the hot and humid Guangzhou area to investigate the thermal benefits of external vertical green walls with varying green coverage and diverse layouts, encompassing effects such as shading, insulation, cooling, and humidification. Analyses were conducted using ENVI-met, orthogonal experiments, and SPSS to quantify the moderating effects of planted green coverage (PGC), leaf area density (LAD), and air interstitial layers on the environmental thermal benefits. The results indicated that the cooling and humidifying effects of 100% PGC and 75% PGC were comparable and superior to those of 50% PGC, yet 75% PGC outperformed 100% PGC in terms of indoor humidification. Among the layout modes, the horizontal layout was the most effective for cooling and humidification, followed by the point layout, with the vertical layout being the least effective. A global sensitivity analysis revealed that PGC had the greatest impact on wall cooling and outdoor humidification, LAD significantly influenced humidification, the width of air interstitial layers had a minor impact, and the two architectural vertical greening design ratios of 75% PGC × 4.60 LAD and 75% PGC × 2.70 LAD were particularly effective for cooling and humidification. Incorporating horizontal or point-like layouts can enhance façade design diversity while preserving the desired environmental thermal benefits, thereby contributing to the overall aesthetics of a building.